Omega-3 fatty acids are associated with a lower prevalence of autoantibodies in shared epitope-positive subjects at risk for rheumatoid arthritis - Gan, Ryan W (Ann Rheum Dis, 2016)
OBJECTIVES: Previously, we found that omega-3 fatty acids (n-3 FAs) were inversely associated with anti-cyclic citrullinated peptide (anti-CCP) positivity in participants at risk for future rheumatoid arthritis (RA). We investigated whether n-3 FAs were also associated with rheumatoid factor (RF) positivity and whether these associations were modified by shared epitope (SE) positivity. METHODS: The Studies of the Etiology of RA (SERA) cohort includes RA-free participants who are at increased risk for RA. We conducted a nested case–control study (n=136) to determine the association between RF and anti-CCP2 positivity and n-3 FA percentage in erythrocyte membranes (n-3 FA% in red blood cells (RBCs)). Additionally, in the baseline visit of the SERA cohort (n=2166), we evaluated the association between reported n-3 FA supplement use and prevalence of RF and anti-CCP2. We assessed SE positivity as an effect modifier. RESULTS: In the case–control study, increasing n-3 FA% in RBCs was inversely associated with RF positivity in SE-positive participants (OR 0.27, 95% CI 0.10 to 0.79), but not SE-negative participants. Similar associations were seen with anti-CCP positivity in SE-positive participants (OR 0.42, 95% CI 0.20 to 0.89), but not SE-negative participants. In the SERA cohort at baseline, n-3 FA supplement use was associated with a lower prevalence of RF positivity in SE-positive participants (OR 0.32, 95% CI 0.12 to 0.82), but not SE-negative participants; similar but non-significant trends were observed with anti-CCP2. CONCLUSIONS: The potential protective effect of n-3 FAs on RA-related autoimmunity may be most pronounced in those who exhibit HLA class II genetic susceptibility to RA.